A study of factors hindering increased production in the Rangitaiki Plains and in Galatea : thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Massey University - Cronin, M B (Massey University, 1968)
This chapter gives a brief outline of the purpose of this study of the Rangitaiki Plains and Galatea. The population of farms from which the survey sample was taken is defined, and a thesis guide is given. 1.2 The Purpose of the Survey Prior to this survey some farmers on the Rangitaiki Plains and in Galatea were making large increases in butterfat production by following a pattern of higher stocking rates, and increased rates of application of fertilizer, together with the required compl ementary inputs. It was noticed, however , by the district extension officers, and officials of the Rangitaiki Plains Dairy Company that many other farmers were remaining static in production. This study consisted of a survey of 37 dairy farms selected from this district, and was aimed to firstly evaluate, both physically and financially, development projects on progressive farms, and secondly to investigate the factors which were hindering other farmers from increasing production, and to find ways of overcoming these problems. [From Introduction]
Keywords: Agricultural productivity; New Zealand; Bay of Plenty Region; Rotorua District